2017
DOI: 10.12659/msm.907840
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Complications in Implant-Supported Dentures: A 4-Year Retrospective Study

Abstract: BackgroundImplants that can be used in the prosthetic rehabilitation of full and partial edentulous patients are now frequently used due to advances in dentistry. Despite advanced methods of applications, failures and complications can still be seen. The aim of our study was to evaluate clinical prosthetic values and complications that occurred during 4-year follow-up in implant-supported restorations.Material/MethodsThis retrospective study included 40 patients who received oral rehabilitation with an implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
10
1
1
Order By: Relevance
“…In our case protocol, peri-operative care was discussed thoroughly with the patient, including the delayed loading protocol and further recall visits needed. The implant CSR in our study was found to be 99%, which is slightly better than the study by Eliasson [ 11 ], where they found it to be 92–94.4% of implant survival rate in the early loading group compared to 98% at the delayed loading group; the result of a five-year recall study [ 10 , 11 ].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In our case protocol, peri-operative care was discussed thoroughly with the patient, including the delayed loading protocol and further recall visits needed. The implant CSR in our study was found to be 99%, which is slightly better than the study by Eliasson [ 11 ], where they found it to be 92–94.4% of implant survival rate in the early loading group compared to 98% at the delayed loading group; the result of a five-year recall study [ 10 , 11 ].…”
Section: Discussioncontrasting
confidence: 71%
“…One retrospective study included 40 patients who had a similar treatment protocol to the one used in our study of the 6IFP plan and were followed for 4 years. The study reported an implant survival rate of 98%, and 100% prosthetic success, except for minor issues that were managed conservatively such as loosening of the abutment screws, mucositis, or prosthesis minor fractures, which were encountered in a few cases in our series [ 10 ]. In our case protocol, peri-operative care was discussed thoroughly with the patient, including the delayed loading protocol and further recall visits needed.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent prosthetic complications after the placement of an implantsupported prosthesis are: mucositis, loosening or fracture of the abutment screw or prosthetic components, and fracture of the acrylic or porcelain structure. Although most complications resolve favorably in follow-up appointments, it is essential to establish an adequate surgical and prosthetic management protocol to achieve predictable and successful long-term results [49,50].…”
Section: Complicationsmentioning
confidence: 99%
“…Prosthodontic complications commonly occur with a removable implant-supported prosthesis, ranging from loss of retention of attachment systems to loosening of screws ( 31 ). Biological emergencies usually include gingival hyperplasia beneath a bar, which can lead to failure of the denture to the seat.…”
Section: Emergencies Related To Prosthesismentioning
confidence: 99%